2022
DOI: 10.1021/acscentsci.1c01153
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Prosthetics for Long-Term Functional Imaging with Fluorescent Reporters

Abstract: Voltage-sensitive fluorescent reporters can reveal fast changes in the membrane potential in neurons and cardiomyocytes. However, in many cases, illumination in the presence of the fluorescent reporters results in disruptions to the action potential shape that limits the length of recording sessions. We show here that a molecular prosthetic approach, previously limited to fluorophores, rather than indicators, can be used to substantially prolong imaging in neurons and cardiomyocytes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…As nanoscopy techniques generally require higher light doses than diffraction-limited approaches, photodamage and photobleaching can become a key, yet often under-evaluated technical hurdle, for analyzing four-dimensional dynamics ( 19 21 ). We previously demonstrated that cyanine-COT conjugates ( 22 26 ) are gentle mitochondrial markers that allow prolonged SIM recordings of cristae ( 25 ) ( SI Appendix , Fig. S1 ).…”
mentioning
confidence: 99%
“…As nanoscopy techniques generally require higher light doses than diffraction-limited approaches, photodamage and photobleaching can become a key, yet often under-evaluated technical hurdle, for analyzing four-dimensional dynamics ( 19 21 ). We previously demonstrated that cyanine-COT conjugates ( 22 26 ) are gentle mitochondrial markers that allow prolonged SIM recordings of cristae ( 25 ) ( SI Appendix , Fig. S1 ).…”
mentioning
confidence: 99%
“…Not surprisingly, therefore, it is possible to modify a potent bilayer-modifying molecule (e.g., resveratrol; Ingólfsson et al, 2014 ), to minimize its bilayer-perturbing effects while maintaining its desired biological effects ( Bosquesi et al, 2020 ). To our knowledge, this is the first example of a drug candidate that was developed with explicit consideration of its bilayer-modifying properties; a similar strategy has been used to minimize the off-target effects of photostabilizers used to protect fluorescent reporter groups ( Grenier et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, photobleaching of traditional reporters makes it challenging to perform prolonged imaging experiments, and phototoxicity results in alterations to neuronal physiology. To bypass these limitations, Miller and co-workers reported a creative approach wherein they appended a cyclooctatetraene (COT) scaffold to a VFdye . The COT group acts as a triplet state quencher (TSQ) to reduce both photobleaching of the dye and phototoxicity toward neurons and cardiomyocytes.…”
Section: Small-molecule Probe Platformsmentioning
confidence: 99%